2014
DOI: 10.2355/isijinternational.54.1705
|View full text |Cite
|
Sign up to set email alerts
|

Carbonitride Dissolution and Austenite Grain Growth in a High Cr Ferritic Heat-resistant Steel

Abstract: Dissolution of carbonitrides and growth of austenite grain in X12CrMoWVNbN10-1-1 steel under various austenitizing conditions were investigated. The experimental results showed that the carbonitrides existing in after-forging heat treated state were mainly Cr23C6 and small amounts of NbN and Cr2N. However, Cr23C6 and Cr2N precipitates were dissolved completely after austenitization at 1 070°C for 60 min or at 1 200°C for 15 min, only the NbN particles left. The state of dissolution of NbN particles was also st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…It was reported that in this steel more than half of these precipitates were not dissolved after austenitization at 1080 • C for 16 h [16]. These dispersed particles exerted a strong pinning force on the growth of austenite grains [9]. In addition to these Nb-rich MN particles, the microstructure of the specimen A also exhibited the need-like Fe-rich M 3 C precipitates.…”
Section: Microstructure After Austenitizationmentioning
confidence: 94%
See 3 more Smart Citations
“…It was reported that in this steel more than half of these precipitates were not dissolved after austenitization at 1080 • C for 16 h [16]. These dispersed particles exerted a strong pinning force on the growth of austenite grains [9]. In addition to these Nb-rich MN particles, the microstructure of the specimen A also exhibited the need-like Fe-rich M 3 C precipitates.…”
Section: Microstructure After Austenitizationmentioning
confidence: 94%
“…1). The carbonitrides present in the asreceived microstructure were mainly Cr-rich M 23 C 6 and a small amount of Nb-rich MN and Cr-rich M 2 N [9]. The heat treatments were performed in an electric resistance furnace.…”
Section: Materials and Heat Treatment Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…8) Additionally, the relationship between dissolution of precipitates and the austenite grain growth of this steel had also been studied. 9) Once the steels have been austenitized, quenching to below the martensite transformation range facilitates the formation of martensite due to its high Cr content. For the large high/middle pressure rotor forging (e.g.…”
Section: Introductionmentioning
confidence: 99%